Application of layered double hydroxides in advanced wastewater remediation processes for the removal of phenol, efavirenz, and nevirapine - Tichapondwa, Shepherd Masimba (University of Pretoria, 2024)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2024.